Shooting straight: telling the truth about guns in America - LaPierre, Wayne R. (Regnery Publ., 2002)
Piggybacking on terror -- Your handbook on gun issues -- Citizens' rights -- (Real) homeland defense -- Gun safety -- Second Amendment follies -- The gun control hive -- The litigation machine -- Hollywood and guns -- Little acorns and bad treaties -- Gun control and silver bullets.